Virtual University modules - Zhanbusinova, B.H.; Iskakova, G.Sh.; Shaukenova, K.S.; Shayakhmetova, B.K.; Mukasheva, A.K. (Bulletin of the Karaganda University. Mathematics Series, 2017)
In the article the questions of filling the modules of the virtual university with teaching methods are considered. The main educational tools used in the content, as well as the types computer training programs.The work with such programs is aimed at mental actions of the student, formation and consolidation of professional skills. In the conditions of modern technologies, creative approach of teaching in professional activity is necessary. The authors show how the functions of teachers, in comparison with the traditional training system, are diversified.